The third record of Smicromyrmilla ariasi (André, 1896) (Hymenoptera: Mutillidae) in the Iberian Peninsula - Allegra Monet Strauss; Daniel Parejo-Pulido; Rafael Matias (Graellsia)
Mutillid wasps (Hymenoptera: Mutillidae) are among the least known species in the biodiverse Iberian Peninsula, in particular those in the primitive subfamily Ticoplinae. Smicromyrmilla ariasi (André, 1896) is hitherto known only from females, and within Iberia by only two specimens, including the holotype. One female mutillid wasp photographed in the foothills of southwestern Sierra Nevada (Granada, Spain) was later identified in a citizen science internet platform as S. ariasi, constituting the third record for the Iberian Peninsula.